Make 'em laugh short-term memories of longtime friends - Reynolds, Debbie 1932-2016; Hannaway, Dorian (William Morrow, an imprint of HarperCollins Publishers, 2016)
The beloved Hollywood star and New York Times bestselling author of Unsinkable continues her intimate chat with fans in this entertaining collection of anecdotes, stories, jokes, and random musings from a woman who has seen it all, and done most of it
Reprint. Originally published: 2015
Keywords: Reynolds, Debbie -- 1932-2016; Schauspielerin; Sängerin; USA; Reynolds, Debbie; Motion picture actors and actresses / United States / Biography; Entertainers / United States / Biography; Entertainers; Motion picture actors and actresses; United States; Biography; Autobiografie; Biografie